PEMASARAN REMAJA (Studi Literatur tentang Pemasaran Barang dan Jasa untuk Remaja) - Herlina, Dyna (Faculty of Economics and Business Universitas Jenderal Soedirman, 2007)
Not until World War II, teen become an important demographic. Their population keep increase every year. Generation Y is the richest teen ever. Moreover, Generation Yalso influence their parents spending. Teenagers fond of fashion and music. Lately they also use credit card. They need education more than adults that for their parents provide the best education services. Marketers need television, internet, video game, peers and parents to encourage them comsume. Because expand of information technology, there are global teenagers. Teenagers all over the world have some similarities on sports, music, fashion and computer. But because of local circumtances they also have differences. So that, marketers should provide different strategy to promote their product in each country. On this article I wrote some important issues about marketing to teenager such as : the history, the importance, products and services, marketing communication, and costumer behaviour of teenager.